Pretreatment of prosthetic valve sewing-ring with the antibiotic/fibrin sealant compound as a prophylactic tool against prosthetic valve endocarditis - Karck, Matthias; Siclari, E.; Wahlig, H.; Sperling, U.; Schmid, C.; Haverich, Axel (European journal of cardio-thoracic surgery, 1990)
Prosthetic valve endocarditis (PVE) remains a dreaded complicationfollowing heart valve replacement despite perioperative antibiotic (AB)prophylaxis. In order to increase the AB concentration in the sewing ring,an experimental study including topical application of the gentamicinderivative EMD 46/217 and fibrin sealant (F) as AB-carrier was initiated.In vitro pretreatment of Dacron with the gentamicin derivative and F wasfollowed by constant AB release for 3 weeks. In a subsequent animal study,four Dacron rings with different pretreatment were implanted in thedescending aorta of 10 pigs after direct contamination with 10(8)Staphylococcus aureus solution. One ring was pretreated with the AB/Fcompound, a second ring with the AB alone. Ring 3 (no pretreatment) andring 4 (F alone) served as controls. After 1 week, the sewing rings andtheir corresponding implantation sites were assayed for measurement ofAB-content and for culture. The AB content of AB/F-rings was 24.99 +/- 7.16micrograms/g wet weight, while rings pretreated with the AB alone containedno measurable drug amounts with the exception of one specimen (0.5microgram/g) (AB/F vs. AB- rings: P less than 0.0005). The correspondingimplantation sites to AB/F rings contained 1.07 +/- 0.54 micrograms/g AB,whereas in only 2 of 10 implantation sites of AB rings, low AB levels werefound (0.05 and 0.2 micrograms/g) (AB/F vs. AB ring implantation sites: Pless than 0.0005). While all control rings and 9 of 10 AB rings wereinfected, 5 of 10 AB/F rings remained sterile after culture (AB/F vs. ABrings: P = 0.05). This finding correlated with the AB content in the suturerings.(ABSTRACT TRUNCATED AT 250 WORDS)